OPTIMALISASI JAM BUKA PERPUSTAKAAN DALAM MENDUKUNG AKTIVITAS AKADEMIK MAHASISWA - Barr, Syekhan Abdil; Fani, Safila Mutiara; Tunggadewi, Priscila Buana; Choirunissa, Rossalya; Nuraji, Sausan Olivia; Al Hakim, Ahmad Rasyid Maulana (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This research was aimed to factually examine the effect of library night operating hours and flexibility of library services on user satisfaction in supporting student academic activities. The analysis used the independent variable of library night operating hours and the dependent variable of user satisfaction. The sample was taken by purposive sampling method. Data collection was done by distributing questionnaires directly to the library users as many as 81 questionnaires. The statistical methods used are validity, reliability, correlation, simple linear regression, and coefficient of determination analysis using IBM SPSS Statistics version 27. The results of this research indicate that the library's night operating hours service and the flexibility of library services have a weak effect on user satisfaction in the Airlangga University Campus B library.